(untitled) (Práxis Educativa, 2023)
This article presents the steps in the construction of the state of knowledge of a research on the life and transformation narratives of early-year teachers. It subsidized a master’s thesis carried out in the year 2022 and expanded the paths that were followed and deepened in it. To carry out the state of knowledge, the methodologies of the authors Morosini and Fernandes (2014) and Morosini, Nascimento and Nez (2021) were used. Having the main characteristics of the method, a survey was carried out on the research carried out on the subject, between the years 2019 and 2021, in the main repositories of theses and dissertations in Brazil. In this research, 17 works were analyzed. In this analysis, it was possible to notice that there is a lot of research on teacher narratives, but there is little that focuses on teachers in the early years. Most studies had beginner teachers or public-school teachers as participants, so there is much to explore in private schools and with experienced teachers.